Low-intensity exercises during chemotherapy infusion for fatigue, functionality, and neuropathy in women with breast cancer - Costa, Brenda Taynara Macedo da; Silva, Simara Cristina Pereira; Vieira, René Aloísio da Costa; Andrade, Carla Elaine Laurienzo da Cunha; Junior, Idam de Oliveira (Mastology, 2026)
To evaluate the practice of low-to-moderate intensity exercise during chemotherapy infusion. Methods: This is a randomized clinical trial with 35 participants, including breast cancer patients aged 18 to 85 years, approved by the ethics committee of the Hospital de Amor, under number 82161424.6.0000.5437. Randomization was performed using sampling on the REDCap platform and consisted of two groups: G1 (intervention) and G2 (control). During the first chemotherapy cycle, questionnaires were administered to assess functionality (IPAQ), fatigue (FAS), chemotherapy-induced neurotoxicity (QNIA), and perceived exertion (Borg scale). For exercise prescription, the maximum heart rate of each patient was calculated. Group G1 was subjected to exercises predefined by the researcher, while group G2 followed the conventional guidelines of the department. After five sessions, participants responded to the study questionnaires and provided feedback created by the researcher. Results: In the final evaluation (after intervention), 28.6% of patients did not experience fatigue, 14.3% had mild fatigue, with severe fatigue being predominant. Regarding functionality, 57.1% became more active after the research period, meeting at least one of the recommendations for frequency and/or duration of physical activity. Considering the degree of neuropathy in the lower limbs, grade 4 (persistent and disabling symptoms) was highlighted in 71.4% of women. In the upper limbs, 50.0% of patients had no symptoms or paresthesia, while the other 50.0% presented grade 4. For orofacial symptoms, grade 3 (pain or functional impairment interfering with activities of daily living) and grade 4 predominated, both at 28.6%. According to the feedback provided by the researcher, physical exercise practice during infusion was beneficial for the patients. Larger-scale studies are needed to confirm their efficacy. The study is still in its inclusion phase.